Central Nervous System Hemangioblastoma in a Pediatric Patient Associated With Von Hippel-Lindau Disease: A Case Report and Literature Review - Yang, Bo; Li, Zhenyu; Wang, Yubo; Zhang, Chaoling; Zhang, Zhen; Zhang, Xianfeng (Frontiers in Oncology, 2021)
Background Hemangioblastoma is a benign tumor of the central nervous system and may appear as a component of von Hippel-Lindau (VHL) disease. At present, approximately 40 cases of optic nerve HGBs have been reported in the literature. VHL disease is a rare autosomal-dominant inherited cancer syndrome with different phenotypes caused by variants in the VHL gene. Herein, the authors describe a case of a pediatric patient with VHL disease and with optic nerve HGB, a rare phenotypic expression. The purpose of this study was to explore the genotype-phenotype, clinical features, treatment and follow-up of VHL-associated hemangioblastomas in pediatric patients. Case Description A 12-year-old boy presented with vision loss, headache and dizziness at our hospital. Magnetic resonance imaging (MRI) revealed a large (19.8 mm*18.5 mm*23.5 mm) irregular mass located in the suprasellar region. The mass was successfully removed after craniotomy and microsurgical treatment. The pathological diagnosis was left optic nerve HGB. Genetic analyses showed p.Pro86Leu (c. 257C>T) heterozygous missense mutations in the VHL gene. Conclusion This is the first reported pediatric case of VHL-associated optic nerve HGB. The genotype-phenotype correlation of VHL disease may provide new evidences for predicting tumor penetrance and survival. Gross tumor resection combined with stereotactic radiosurgery might be the most beneficial treatment.